Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Alright, let's solve the given rational equation step-by-step and identify the solutions and extraneous solutions.
Given equation:
[tex]\[ \frac{3}{x^2 + 5x + 6} + \frac{x-1}{x+2} = \frac{7}{x+3} \][/tex]
### Step 1: Factor the denominators
First, we factor the quadratic denominator to simplify our work with the least common denominator (LCD).
[tex]\[ x^2 + 5x + 6 = (x + 2)(x + 3) \][/tex]
### Step 2: Determine the LCD
The least common denominator (LCD) of \(x^2 + 5x + 6\), \(x + 2\), and \(x + 3\) is:
[tex]\[ \text{LCD} = (x + 2)(x + 3) \][/tex]
### Step 3: Multiply both sides by the LCD
We multiply both sides of the equation by the LCD to eliminate the denominators:
[tex]\[ (x+2)(x+3) \left(\frac{3}{(x + 2)(x + 3)} + \frac{x-1}{x + 2}\right) = (x+2)(x+3) \left(\frac{7}{x + 3}\right) \][/tex]
### Step 4: Simplify the equation
Simplify each term:
[tex]\[ 3 + (x - 1)(x + 3) = 7(x + 2) \][/tex]
Distribute and combine like terms:
[tex]\[ 3 + x^2 + 2x - 3 = 7x + 14 \][/tex]
[tex]\[ x^2 + 2x = 7x + 14 \][/tex]
### Step 5: Rearrange the equation
Move all terms to one side of the equation:
[tex]\[ x^2 + 2x - 7x - 14 = 0 \][/tex]
[tex]\[ x^2 - 5x - 14 = 0 \][/tex]
### Step 6: Solve the quadratic equation
We solve the quadratic equation by factoring, if possible, or using the quadratic formula. This factors nicely as:
[tex]\[ (x - 7)(x + 2) = 0 \][/tex]
This yields the solutions:
[tex]\[ x = 7 \quad \text{or} \quad x = -2 \][/tex]
### Step 7: Check for extraneous solutions
We substitute each solution back into the original equation to check if it is valid. Solutions that make any denominator zero are extraneous.
For \( x = 7 \):
- The denominators \( x^2 + 5x + 6 \), \( x + 2 \), and \( x + 3 \) are all non-zero.
[tex]\[ x^2 + 5x + 6 = 49 + 35 + 6 = 90 \neq 0 \][/tex]
[tex]\[ x + 2 = 7 + 2 = 9 \neq 0 \][/tex]
[tex]\[ x + 3 = 7 + 3 = 10 \neq 0 \][/tex]
So, \( x = 7 \) is a valid solution.
For \( x = -2 \):
- The denominators \( x + 2 \) is zero:
[tex]\[ x + 2 = -2 + 2 = 0 \][/tex]
This makes \( x = -2 \) an extraneous solution.
### Final Results
Thus, the solution to the equation is:
[tex]\[ x = 7 \quad \text{(valid solution)} \][/tex]
[tex]\[ x = -2 \quad \text{(extraneous solution)} \][/tex]
Given equation:
[tex]\[ \frac{3}{x^2 + 5x + 6} + \frac{x-1}{x+2} = \frac{7}{x+3} \][/tex]
### Step 1: Factor the denominators
First, we factor the quadratic denominator to simplify our work with the least common denominator (LCD).
[tex]\[ x^2 + 5x + 6 = (x + 2)(x + 3) \][/tex]
### Step 2: Determine the LCD
The least common denominator (LCD) of \(x^2 + 5x + 6\), \(x + 2\), and \(x + 3\) is:
[tex]\[ \text{LCD} = (x + 2)(x + 3) \][/tex]
### Step 3: Multiply both sides by the LCD
We multiply both sides of the equation by the LCD to eliminate the denominators:
[tex]\[ (x+2)(x+3) \left(\frac{3}{(x + 2)(x + 3)} + \frac{x-1}{x + 2}\right) = (x+2)(x+3) \left(\frac{7}{x + 3}\right) \][/tex]
### Step 4: Simplify the equation
Simplify each term:
[tex]\[ 3 + (x - 1)(x + 3) = 7(x + 2) \][/tex]
Distribute and combine like terms:
[tex]\[ 3 + x^2 + 2x - 3 = 7x + 14 \][/tex]
[tex]\[ x^2 + 2x = 7x + 14 \][/tex]
### Step 5: Rearrange the equation
Move all terms to one side of the equation:
[tex]\[ x^2 + 2x - 7x - 14 = 0 \][/tex]
[tex]\[ x^2 - 5x - 14 = 0 \][/tex]
### Step 6: Solve the quadratic equation
We solve the quadratic equation by factoring, if possible, or using the quadratic formula. This factors nicely as:
[tex]\[ (x - 7)(x + 2) = 0 \][/tex]
This yields the solutions:
[tex]\[ x = 7 \quad \text{or} \quad x = -2 \][/tex]
### Step 7: Check for extraneous solutions
We substitute each solution back into the original equation to check if it is valid. Solutions that make any denominator zero are extraneous.
For \( x = 7 \):
- The denominators \( x^2 + 5x + 6 \), \( x + 2 \), and \( x + 3 \) are all non-zero.
[tex]\[ x^2 + 5x + 6 = 49 + 35 + 6 = 90 \neq 0 \][/tex]
[tex]\[ x + 2 = 7 + 2 = 9 \neq 0 \][/tex]
[tex]\[ x + 3 = 7 + 3 = 10 \neq 0 \][/tex]
So, \( x = 7 \) is a valid solution.
For \( x = -2 \):
- The denominators \( x + 2 \) is zero:
[tex]\[ x + 2 = -2 + 2 = 0 \][/tex]
This makes \( x = -2 \) an extraneous solution.
### Final Results
Thus, the solution to the equation is:
[tex]\[ x = 7 \quad \text{(valid solution)} \][/tex]
[tex]\[ x = -2 \quad \text{(extraneous solution)} \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.